Borland C++BuilderT 6 Developer's Guide - Swart, Bob (Sams, 2011)
C++Builder 6 Developer's Guide is revised for the latest version of C++Builder, the biggest update to C++Builder in years. C++Builder is an ANSI C++ IDE. The Version 6 adds BizSnap, a tool to build Web Services using XML/SOAP, .NET, and BizTalk from Microsoft, and SunONE from Sun Microsystems. Other new components include WebSnap for Web application development, DataSnap for database development, and CLX, which allows cross-platform development for Unix and Linux. The new NetCLX Internet components allow development of cross-platform applications with Apache, Microsoft IIS, and Netscape Web Server applications. C++Builder 6 Developer's Guide continues as the definite guide for Borland's C++Builder, providing a clear and concise reference for C++ Developers.